From Land Conservation to Famers’ Income Growth: How Advanced Livelihoods Moderate the Income-Increasing Effect of Land Resources in an Ecological Function Area - Xinyu Zhang; Yiqi Zhang; Yanjing Yang; Wenduo Wang; Xueting Zeng (Land)
Balancing ecological conservation and rural livelihoods in protected areas remains a global challenge, particularly under strict land use regulations and economic development constraints. Territorial spatial planning (TSP) in an ecological function area (EFA) faces constraints such as land use restrictions, ecological redlines, and economic development limits. This study investigates how ecological land resources influence farmers’ incomes in ecological function areas (EFAs), with a focus on the moderating role of advanced livelihoods (ALI). Using an integrated Fixed-Effects–SVM–Genetic Algorithm framework, we quantify nonlinear policy-livelihood interactions and simulate multi-scenario governmental interventions (e.g., ecological investment, returning farmland to forest/RFF) across Beijing’s EFA, which can obtain the key findings as follows: (a) Ecological land resources have a significant positive effect on farmers’ incomes due to production-manner adjustment guided by governmental green strategy and corresponding TSP in an ecological restoration area of an EFA, while they have a non-significant impact in the core ecological reserve areas on account of the strict environmental protection restrictions on economic activities. (b) Differences in financial support between lower and higher economic development zones can bring about adverse impact results on farmers’ incomes in an EFA. (c) ALI significantly amplifies the positive impact of ecological land use on farmers’ incomes, demonstrating its critical role in bridging ecological and economic goals. (d) Sensitivity analysis results under RFF, targeted government investment, and ALI can maximize income gains through policy interaction from the government and farmer sides jointly. The above obtained results are beneficial to balance ecological protection and economic interests of farmers’ sustainably in an EFA.